2017
DOI: 10.5944/rppc.vol.22.num.3.2017.18848
|View full text |Cite
|
Sign up to set email alerts
|

Perfiles de personalidad y síndromes clínicos en personas sin hogar

Abstract: Abstract:The aims of this study were to examine the presence of clinical personality patterns and clinical syndromes in homeless, and to identify common personality profi les. Participants were 144 subjects, 35 women and 109 men (mean age = 42 years), all of them in a situation of chronic social exclusion, 67% were homeless for more than a year, and 33% more than three years. During the evaluation period they resided in a shelter for the homeless. Results showed that clinical personality patterns and clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Thus, the mean international prevalence is between 0.42% (Lombardi et al, 2020) and 23.1% (Fazel et al, 2008). The results of the study are therefore consistent with this, although our analysis shows a prevalence that is lower than that found in other Spanish studies (Rodríguez-Pellejero et al, 2017;Salavera et al, 2009).…”
Section: The Mental Health Of Individuals Experiencing Homelessnesssupporting
confidence: 90%
“…Thus, the mean international prevalence is between 0.42% (Lombardi et al, 2020) and 23.1% (Fazel et al, 2008). The results of the study are therefore consistent with this, although our analysis shows a prevalence that is lower than that found in other Spanish studies (Rodríguez-Pellejero et al, 2017;Salavera et al, 2009).…”
Section: The Mental Health Of Individuals Experiencing Homelessnesssupporting
confidence: 90%
“…There is a relatively extensive line of research examining the impact and scale of mental health problems affecting PSH. Studies have notably examined life events that act as stressors and are more prevalent among PSH than among the general population [11,27], such as depressive symptoms and other mental illnesses [28,29] and suicide attempts [30].…”
Section: Homeless and Mental Healthmentioning
confidence: 99%
“…There was a notably high average score for GHQ-12 (average = 5.03; SD = 3.41), indicating high levels of psychological impairment. Taking into account the cut-off point that was used (equal to or greater than 3) [28], 66.9% of the study participants reported impaired mental health. On the other hand, a majority of the participants gave a positive assessment of their general state of health (87.4%).…”
Section: Descriptive and Bivariate Analysesmentioning
confidence: 99%